Peningkatan Kemampuan Komunikasi Matematis Siswa SMP Melalui Pembelajaran Inkuiri Model Alberta - Usman, Muhammad Rizal (Pendidikan Matematika Universitas PGRI Yogyakarta, 2017)
This research is motivated by the results of previous research which shows that students' mathematical communication ability is still not as expected. The focus of this research is to determine the improvement of students' mathematical communication ability as a result of the investigation of the Alberta model learning. This research is experimental research with the population of all students of one of the State Junior High School in Bandung. The sample of the research is the grade VII students of the school. Samples were 73 students, 36 students of experimental class and 37 students of the control class. Based on the results of data analysis, it can be concluded that: (1) The achievement of mathematical communication ability of students who gain learning inquiry model Alberta better than students who learn conventional, (2) Improve the ability of mathematical communication, the thinking of students who gain learning inquiry model Alberta better than students Gain conventional learning, and (3) there is a difference in improving the ability of mathematical communication thinking based on the category of early mathematical ability.Keywords: Mathematical Communication Ability, Alberta Model Inquiry